Direct modulation of TRPC ion channels by Gα proteins - Kang, Hana; Kim, Jinhyeong; Park, Christine Haewon; Jeong, Byeongseok; So, Insuk (Frontiers in Physiology, 2024)
GPCR-Gi protein pathways are involved in the regulation of vagus muscarinic pathway under physiological conditions and are closely associated with the regulation of internal visceral organs. The muscarinic receptor-operated cationic channel is important in GPCR-Gi protein signal transduction as it decreases heart rate and increases GI rhythm frequency. In the SA node of the heart, acetylcholine binds to the M2 receptor and the released Gβγ activates GIRK (I(K,ACh)) channel, inducing a negative chronotropic action. In gastric smooth muscle, there are two muscarinic acetylcholine receptor (mAChR) subtypes, M2 and M3. M2 receptor activates the muscarinic receptor-operated nonselective cationic current (mIcat, NSCC(ACh)) and induces positive chronotropic effect. Meanwhile, M3 receptor induces hydrolysis of PIP2 and releases DAG and IP3. This IP3 increases intracellular Ca 2+ and then leads to contraction of GI smooth muscles. The activation of mIcat is inhibited by anti-Gi/o protein antibodies in GI smooth muscle, indicating the involvement of Gαi/o protein in the activation of mIcat. TRPC4 channel is a molecular candidate for mIcat and can be directly activated by constitutively active Gαi QL proteins. TRPC4 and TRPC5 belong to the same subfamily and both are activated by Gi/o proteins. Initial studies suggested that the binding sites for G protein exist at the rib helix or the CIRB domain of TRPC4/5 channels. However, recent cryo-EM structure showed that IYY 58-60 amino acids at ARD of TRPC5 binds with Gi3 protein. Considering the expression of TRPC4/5 in the brain, the direct G protein activation on TRPC4/5 is important in terms of neurophysiology. TRPC4/5 channels are also suggested as a coincidence detector for Gi and Gq pathway as Gq pathway increases intracellular Ca 2+ and the increased Ca 2+ facilitates the activation of TRPC4/5 channels. More complicated situation would occur when GIRK, KCNQ2/3 (IM) and TRPC4/5 channels are co-activated by stimulation of muscarinic receptors at the acetylcholine-releasing nerve terminals. This review highlights the effects of GPCR-Gi protein pathway, including dopamine, μ-opioid, serotonin, glutamate, GABA, on various oragns, and it emphasizes the importance of considering TRPC4/5 channels as crucial players in the field of neuroscience.